Examining Suicidal Thoughts and Behaviors Among Ohio Youth with Oppressed Identities Using the 2019 Ohio Youth Risk Behavior Survey - C. Rosie Bauder; Austin G. Starkey (Ohio Journal of Public Health, 2023)
Background: Suicide is the second leading cause of death among youth aged 10 to 14 years and third for those aged 15 to 24 years in the United States and in Ohio. Suicidal thoughts and behaviors disparately affect youth with oppressed identities, including those with oppressed racial, ethnic, gender, and sexual minority identities. The purpose of this study was to examine the relationship between self-reports of suicidal thoughts and behaviors among Ohio youth with oppressed identities. This research also contextualizes relationships between these indicators through the context of intersectionality. Methods: This cross-sectional descriptive study used responses from the 2019 Ohio Youth Risk Behavior Survey (YRBS; n = 1263) to examine the relationships between identity variables and suicidal thoughts and behaviors through a series of logistic regression models. Results: Female youth have higher odds of reporting persistent feelings of sadness and hopelessness and seriously considering suicide than male youth. Lesbian, gay, or bisexual (LGB) youth have higher odds of reporting all outcome measures of suicidal thoughts and behaviors (STBs), and youth with oppressed racial and ethnic identities were in general more likely to report higher odds of STBs when compared to White youth. Conclusion: Suicidal thoughts and behaviors disparately affect youth with these oppressed identities. Our findings suggest further examination of these youth nationally may influence public health suicide prevention strategies. Implica-tions also suggest that researchers, practitioners, and organizations across the spectrum of youth suicide prevention in Ohio should understand the increased risk that youth with multiple, intersectional oppressed identities face for suicide.
Keywords: Suicide; Youth Risk Behavior Survey; YRBS; Intersectionality; Ohio youth; Oppressed identities